Routing in mobile Ad Hoc Networks - Pathan, Al-Sakib Khan; Hong, Choong Seon (Springer, 2009)
A Mobile Ad Hoc Network (MANET) is built on the fly where a number of wireless mobile nodes work in cooperation without the engagement of any centralized access point or any fixed infrastructure. Two nodes in such a network can communicate in a bidirectional manner if and only if the distance between them is at most the minimum of their transmission ranges. When a node wants to communicate with a node outside its transmission range, a multihop routing strategy is used which involves some intermediate nodes. Because of the movements of nodes, there is a constant possibility of topology change in MANET. Considering this unique aspect of MANET, a number of routing protocols have been proposed so far. This chapter gives an overview of the past, current, and future research areas for routing in MANET. In this chapter we will learn about the following things: - The preliminaries of mobile ad hoc network - The challenges for routing in MANET - Expected properties of a MANET routing protocol - Categories of routing protocols for MANET - Major routing protocols for MANET - Criteria for performance comparison of the routing protocols for MANET - Achievements and future research directions - Expectations and reality